2012
DOI: 10.1016/j.febslet.2012.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Two sides of the story? Smad4 loss in pancreatic cancer versus head‐and‐neck cancer

Abstract: TGFβ signaling Smads (Smad2, 3, and 4) were suspected tumor suppressors soon after their discovery. Nearly two decades of research confirmed this role and revealed other divergent and cancer-specific functions including paradoxical tumor promotion effects. Although Smad4 is the most potent tumor suppressor, its functions are highly context-specific as exemplified by pancreatic cancer and head-and-neck cancer: in pancreatic cancer, Smad4 loss cannot initiate tumor formation but promotes metastases while in head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 122 publications
(196 reference statements)
4
59
0
Order By: Relevance
“…However, in contrast to male rats, middle-aged female rats demonstrated an increase in Smad4 mRNA expression in the reproductive organs (ovaries and uterus) relative to the pubertal and young adult groups. Given the role of Smad4 as a tumor suppressor 24 , these changes may be indicative of the Smad4 related anti-proliferative mechanisms induced in aging female rats as reproductive activity declines 25 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast to male rats, middle-aged female rats demonstrated an increase in Smad4 mRNA expression in the reproductive organs (ovaries and uterus) relative to the pubertal and young adult groups. Given the role of Smad4 as a tumor suppressor 24 , these changes may be indicative of the Smad4 related anti-proliferative mechanisms induced in aging female rats as reproductive activity declines 25 .…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β may serve as tumour suppressor, but in the advanced stage of cancer it may paradoxically hasten progression of the disease, for example by induction of epithelial-to-mesenchymal transition (EMT) [23][24][25]. The tumour suppressor gene SMAD4/DPC4/MADH4 is a core component of the TGF-β signaling pathway [17,21,23,26,27]. According to recent studies, SMAD4 plays a pivotal role in the development of metastatic PDAC [17,19,20,28].…”
Section: Introductionmentioning
confidence: 99%
“…Underscoring the tumor-suppressing role of TGF-b, mutations of TGFbRI, TGFbRII, and SMAD4 are frequently identified in gastrointestinal, pancreatic, breast, head and neck, and cervical cancers. 2,3,10 Paradoxically, SMAD3 mutations are rarely seen …”
mentioning
confidence: 99%
“…Underscoring the tumor-suppressing role of TGF-b, mutations of TGFbRI, TGFbRII, and SMAD4 are frequently identified in gastrointestinal, pancreatic, breast, head and neck, and cervical cancers. 2,3,10 Paradoxically, SMAD3 mutations are rarely seen in tumors, despite its close structural and functional similarity to SMAD4. Moreover, interrogation of pancreatic and colon cancer genomics has found that SMAD4 mutations usually occur during late stages of tumorigenesis and are prognostic indicators of metastasis, advanced diseases, and reduced survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation